October 2022 Placement Ads (The Accounting Review, 2022)
The deadline for free position ads to be included in this section of The Accounting Review is two months prior to the desired publication in the January, March, May, July, September, or November issues. Position ads, which are free with the purchase of a job posting in the AAA Career Center, should provide all relevant information about the available positions and must include contact information or application instructions for interested candidates. For more information on how to purchase a job posting in the Career Center, or for updated, detailed information about the placement listings in this issue, please go to the AAA website at http://aaahq.org and click on “Career Center,” or call our office at 941-921-7747.AHLIA UNIVERSITY seeks candidates for a position as Assistant/Associate Professor in Forensic Accounting (full-time/part-time). Requirements: Ph.D. in Forensic Accounting Fraud Examination or related field from a recognized Institution. Teaching Experience is preferable. Excellent communication skills in English. To apply please go to: https://www.ahlia.edu.bh/vacancies/HAEFELE, FLANAGAN & CO. seeks candidates for a position as a Training Specialist, full-time during Tax Season. This is an excellent and unique opportunity for a retired CPA or accounting college professor. The Training Specialist will assist professional staff with driving tax returns (business and individual) to completion and to maintain and assist the growth of the training curriculum for our tax team. During the course of the day, staff will report to the Tax Team Training Specialist for general knowledge or to support the staff with software or tax related questions ensuring our clients with accurate preparation and filing. Must have experience with most of the following applications: CCH Access Tax and Workstream; Thomson Reuters Advanced Flow; Go File Room; SurePrep; TaxCaddy; and Microsoft Teams. To apply please visit: https://haefeleflanaganco.applytojob.com/apply/u7mRFomvq6/Tax-Department-Training-SpecialistLOYOLA UNIVERSITY CHICAGO, Quinlan School of Business, Department of Accounting and Business Law is accepting applications for a tenure-track position in Accounting at the Senior Assistant or Associate Professor rank (subject to budgetary funding and approval) with a Fall 2023 start date. Applicants must possess a Doctorate in Accounting from an AACSB-accredited institution. Teaching responsibilities will be both at the undergraduate and M.S.A./M.B.A. levels. Area of interest must include Accounting Analytics. Required qualifications include published research in high-quality-level accounting journals, teaching excellence, and a strong commitment to service and the profession. Professional accounting certification (e.g., CPA) is expected. We offer a highly competitive compensation package. Social justice, diversity, equity, and inclusion being core elements of the University's mission, the Department of Accounting and Business Law encourages individuals from underrepresented racial and ethnic groups to apply for the position. Referees will not be contacted immediately but might be at subsequent points in the review process. Inquiries may be directed to: Brian Stanko, Professor and Search Committee Chair, Quinlan School of Business, Department of Accounting and Business Law, Loyola University Chicago, 16 East Pearson, Suite 506, Chicago, IL 60611; Phone: (312) 915-7106.BELLARMINE UNIVERSITY, W. Fielding Rubel School of Business has an opening for the position of Endowed Chairperson, Department of Accounting. In alignment with the University's values, priorities, and commitment, we seek an individual who is dedicated to and invested in equity and inclusiveness. The Chair serves as the Department Administrator and as a representative for the accounting program to both internal and external stakeholders. Internally, the Chair engages in teaching, research/scholarly activity, and with students via the accounting association and internship programs. Externally, the Chair will nurture and develop relationships with the accounting community and alumni. The Chair reports to the Dean of the School of Business. This position is a 12-month tenure-track, or tenured-based on experience, faculty position at the Associate/Full Professor rank (based on experience) beginning July 1, 2023. Salary is competitive and commensurate with qualifications. Go to: https://bellarmine.interviewexchange.com/jobofferdetails.jsp?JOBID=151669&CNTRNO=1&TSTMP=1663433411786UTAH VALLEY UNIVERSITY, Woodbury School of Business, Department of Accounting has a tenure-track position beginning August 2023. While all areas of accounting will be considered, preference will be given to applicants with expertise in taxation. Graduation with a Ph.D. in accounting/taxation from an AACSB-accredited institution is required. ABDs nearing completion of their degree may be considered. Evidence of high-quality teaching as well as quality research potential is required of all applicants. The Woodbury School of Business is accredited by AACSB, while maintaining a teaching-focused mission consistent with that of Utah Valley University. The Department offers both undergraduate and graduate degrees in accounting. Utah Valley University is located in Orem, Utah, about 45 minutes from downtown Salt Lake City and the Salt Lake International Airport. Please contact Dr. Joel Helquist, Chair of the Department of Accounting (JoelH@uvu.edu) for more information.MONTCLAIR STATE UNIVERSITY, Feliciano School of Business, Department of Accounting and Finance invites applications for a full-time tenure-track faculty position in the at the Assistant or Associate Professor level, Financial Accounting/Analytics, starting September 1, 2023. Candidates holding tenure at their current institution are invited to apply. The candidate selected will be expected to teach courses at both the undergraduate and graduate levels in face-to-face and online delivery modes. Candidates with experience in developing and/or teaching in online formats will be given preference. Go to: https://montclair.wd1.myworkdayjobs.com/en-US/JobOpportunities/job/Assistant-Associate-Professor-Financial-Accounting-Analytics_R1002542DEPAUL UNIVERSITY, School of Accountancy & MIS seeks to fill two tenure-track Assistant Professor positions with a teaching focus in accounting information systems, data analytics, and/or financial accounting to begin Fall 2023. Candidates should possess a doctorate or be close to completion of a doctorate in accounting from an AACSB-accredited university. The ideal candidate will be able to teach courses at both the undergraduate and graduate levels. Candidates should also demonstrate potential for success in conducting quality research in the field of accounting. Salary and benefits are competitive with AACSB schools. Review of applications will begin immediately and will continue until the positions are filled. Go to: https://account.interfolio.com/login?apply=109725TENNESSEE STATE UNIVERSITY, College of Business invites applicants for the Frist Chair of Excellence in Business with focus on Accounting. The Chair holder should be a distinguished scholar and bring prestige to the position and the College of Business. This is a nine-month faculty position with special duties as holder of the Frist Chair of Excellence (#102680) with rank open for consideration and may begin as early as January 1, 2023. The ideal candidate must possess the following: (a) an earned doctorate in accounting or the equivalent, (b) a distinguished and stellar record of scholarly publications, and (c) teaching and service in the field of accountancy. CPA certification with recent public or industry accounting experience preferred. The candidate must be a visionary and show evidence of community outreach endeavors related to advancing the accounting profession as well as possess external fundraising experience. Salary and rank commensurate with education and experience. Contact: Eva K. Jermakowicz, Ph.D., CPA Department Chair (Interim), ejermakowicz@tnstate.edu.GEORGIA INSTITUTE OF TECHNOLOGY, Scheller College of Business in Atlanta, Georgia is seeking to hire one tenure-track academic faculty in Accounting at the rank of Assistant Professor, beginning Fall 2023. A Ph.D. in Accounting or related discipline is the minimum requirement (Ph.D. must be awarded no later than July 1, 2023). Faculty will be required to be research-active, teach three semester courses per year at the undergraduate/graduate levels, and provide service to the College and accounting profession. Salary is competitive with leading research universities, with opportunities for involvement in executive programs. Please visit: https://bit.ly/3Bb6wNM to submit a cover letter, vita, two research papers, and three letters of recommendation, preferably by December 31, 2022. Georgia Tech is an EEO employer and values diversity, and will not discriminate against any employee or applicant on the basis of any classification protected by federal, state, or local law.UNIVERSITY OF MISSOURI, Trulaske College of Business, School of Accountancy in Columbia, MO invites applications for a tenure-track position beginning in the 2023–2024 academic year. Applicants will be considered for appointment at the rank of Assistant Professor and will be expected to conduct research and teach in the area of Taxation. The School of Accountancy currently has 12 tenured or tenure-track faculty, all of whom are research active. Please go to: https://hrs.missouri.edu/find-a-job/academic (Job ID 42055).UNIVERSITY OF MISSOURI, Trulaske College of Business, School of Accountancy in Columbia, MO invites applications for a non-tenure track teaching faculty position in the area of taxation with a preferred start date of Spring 2023 or Fall 2023. The typical teaching load is 12 credit hours per semester with teaching obligations that include both introductory and advanced tax courses. Please go to: https://hrs.missouri.edu/find-a-job/academic (Job ID 42058)UNIVERSITY OF MISSOURI, Trulaske College of Business, School of Accountancy in Columbia, MO invites applications for a tenured faculty position beginning in August 2023. This position is for the rank of either Associate or Full Professor. Our ideal candidate will have an established research reputation as evidenced by an active and strong record of scholarly achievements. The appointee is expected to continue to pursue research and scholarship and serve as a mentor and advisor to doctoral students and early career faculty. All areas of accounting research will be considered, but the use of archival methods is preferred. The School of Accountancy is strongly interested in recruiting an individual who can embrace and enhance the vision of a diverse, collegial, and productive academic environment. Please go to: hrs.missouri.edu/find-a-job/academic (Job ID 42060).DARTMOUTH UNIVERSITY, Tuck School of Business invites applications for a tenure-track, new Assistant Professor position in accounting beginning in the 2023–24 academic year. To ensure full consideration, candidates should submit all materials by November 18, 2022. Qualifications: We seek candidates who will produce world-class research at a level consistent with Tuck's high standards. Candidates must be able to interact effectively with others and enhance the intellectual environment of the school. Applicants must have, or be near completion of, a Ph.D. in accounting or a related field. The Ph.D. must be completed before the appointment begins. Dartmouth is highly committed to fostering a diverse and inclusive population of students, faculty, and staff. We are especially interested in applicants who are able to work effectively with students, faculty, and staff from all backgrounds, including but not limited to: racial and ethnic minorities, women, individuals who identify with LGBTQ communities, individuals with disabilities, individuals from lower income backgrounds, and/or first-generation college graduates. Applicants should state in their cover letter how their teaching, research, service, and/or life experiences prepare them to advance Dartmouth's commitments to diversity, equity, and inclusion. Application instructions: Faculty applications and all supporting documents must be submitted to: https://apply.interfolio.com/110100WILLAMETTE UNIVERSITY is seeking applicants for a position as Assistant Professor of Accounting. Candidates from all accounting disciplines will be considered, although we are especially interested in candidates whose research has clear managerial and/or policy implications. Applicants should be able and willing to teach an introductory accounting course at both the graduate and undergraduate levels. We also welcome candidates with innovative course ideas that they would like to propose and develop for graduate elective courses. The teaching load will be 2/2. Diversity contributes to academic excellence and to rich and rewarding communities. Willamette University is committed to recruiting and retaining a diverse faculty, staff, and student body. We seek candidates, particularly those from historically under-represented groups, whose work furthers diversity and who bring to campus varied experiences, perspectives, and backgrounds. To be considered for employment at Willamette University, please complete our online employment application. Your application and all required attachments must be submitted for each individual job post that you are interested in applying for. If there is an application deadline, please ensure that your application is submitted by the deadline. Once you submit your application you will not be able to edit your application. Applications will be reviewed on a rolling basis and will continue to be considered until a candidate has been identified. Questions about the position may be directed to the Search Committee Chair: Romana Autrey (rautrey@willamette.edu), Associate Dean for Academic Affairs and Associate Professor of Accounting. Go to: https://willamette.wd1.myworkdayjobs.com/willametteuniversityjobsTHE UNIVERSITY OF TEXAS AT SAN ANTONIO, Department of Accounting, Alvarez College of Business at UTSA is seeking applications for a tenure-track/tenured faculty position at the rank of Assistant or Associate Professor of Accounting with expertise in Accounting Information Systems, Big Accounting Data Analysis, Cyber Security applications for accountants, and the role of Artificial Intelligence in the area of auditing beginning in August 2023. UTSA is a Hispanic-Serving University with more than 34,000 students. UTSA, a premier public research university with a Carnegie R1 classification and NRUF designation, fosters academic excellence through a community of dialogue, discovery, and innovation that embraces the uniqueness of each voice. Interested candidates can contact Dr. Dennis Lopez (dennis.lopez@utsa.edu), Chair of the Search Committee for more information.POTRERO GROUP National Outdoor Leadership School (NOLS) is searching for an extraordinary Chief Financial Officer to lead all aspects of the organization's financial operations and investments. This role will require approximately four to six months of onboarding time at NOLS Headquarters in Lander, Wyoming. At that point, the position will be eligible for long-term hybrid office and remote work options and opportunities for an alternative, non-traditional work schedule. Location within a day's drive of Lander will make work coordination much easier but is not required. A competitive compensation package, including a comprehensive benefits package, will be offered based on experience. The expected annual salary range for this position is 167,000–180,000. Visit: https://potrerogroup.com/executive-search/nols-cfo/, and select “Apply Here.” More information on NOLS can be found at: https://www.nols.edu/. For additional information regarding this opportunity, please contact nolscfosearch@potrerogroup.com.DEAKIN BUSINESS SCHOOL, Deakin Business School, Department of Finance is seeking a dynamic Professor and Associate Professor to develop the discipline of Finance to drive research and education with impact. This is an opportunity to contribute to a world-class business school at a comprehensive University on a steep upward trajectory. The Department of Finance comprises over 40 faculty recognized globally for work in areas like corporate finance, asset pricing, banking and financial intermediation, international finance, financial derivative instruments, and real estate. Deakin has both EQUIS and AACSB accreditation. These roles will serve the Department through teaching, research impact and quality, staff mentoring, industry engagement, and institutional collaboration both nationally and internationally. Appointees will have a strong record in publication, doctoral supervision, research income and educational innovation. For further information please contact Evelyn Richards at: evelyn.richards@perrettlaver.com; or on +61 (0) 2 8075 4610.SANTA CLARA UNIVERSITY invites applicants for an Instructor for their Certificate of Advanced Accounting Proficiency (CAAP) program. CAAP is an intensive weekend program for Post-Baccalaureate students. Classes will be held in-person on five Sundays (May 28, 2023 to June 25, 2023). Applicants must have an established record of quality teaching in Auditing and hold a tenured or tenure-track position at an accredited college or university. Compensation is $16,995. Contact Professor Susan Parker (sparker@scu.edu) for more information. Please apply by emailing Taylor Ganti (TGanti@scu.edu) with your vita, expression of interest, and student evaluations from recent in-person teaching. Applications will be reviewed starting August 24th.CHRISTOPHER NEWPORT UNIVERSITY, Joseph W. Luter, III School of Business invites applications for two tenure-track positions at the Assistant or Associate level in Accounting, effective August 2023. Christopher Newport University (CNU) will make a reasonable effort to accommodate persons with disabilities in the application and/or interview process. For full details on the position, and to apply, please visit: https://jobs.cnu.edu/postings/13942/. Review of applications will begin on October 2, 2022. Applications received after October 2, 2022 will be accepted but considered only if needed. Search finalists are required to complete a CNU-sponsored background check. Persons with disabilities who require accommodation should contact the CNU Human Resources Office by calling (757) 594-7145. Christopher Newport University, an EO Employer, is fully committed to access and opportunity.WESTERN KENTUCKY UNIVERSITY, Gordon Ford College of Business, Accounting Department invites applications for a tenure track position at the Assistant or Associate Professor rank. Employment begins Fall 2023 or earlier. The Gordon Ford College of Business is AACSB-accredited in both business and accounting. Of the 2,000+ students enrolled in the college, more than 300 are accounting majors. The normal teaching load is nine hours per semester. Qualifications include an earned doctorate with an emphasis in Accounting from an AACSB-accredited U.S. institution. ABDs near completion may also be considered. The successful candidate should demonstrate potential for quality teaching, research, and service activities. Additional consideration will be given to applicants with professional certifications and specializations in auditing, taxation, or AIS. Review of qualified applications will begin on August 7, 2022 and continue until the position is filled. Please apply at: https://www.interviewexchange.com/jobofferdetails.jsp?JOBID=150919IOWA STATE UNIVERSITY, Debbie and Jerry Ivy College of Business, Accounting Department invites applications for a tenured/tenure-eligible position as Associate or Full Professor to start August 2023. This is a full-time, nine-month appointment. Responsibilities include continuing to develop and direct a Ph.D. Program in Accounting (if approved), while also conducting high-quality research, teaching at both the graduate and undergraduate levels, and providing service at the Department, College, and University levels. Review of applicants will begin October 10, 2022 and will continue as needed until a pool of qualified applicants is identified. To apply for this position, please click on the link and then “Apply”: https://isu.wd1.myworkdayjobs.com/en-US/IowaStateJobs/details/Assistant–Associate-or-Full-Professor-of-Accounting_R9248?jobFamilyGroup=ad349100dff401ea127be90a060a22e3&jobFamily=ad349100dff4013091911105060a0ae3/, and complete the Employment Application. Please be prepared to enter or attach the following: (1) resume/curriculum vitae, (2) letter of application/cover letter, and (3) contact information for three references.GOVERNORS ISLAND CORPORATION, Senior Accountant, New York, NY is seeking applications. Position duties: Maintain/enforce accounting policies, procedures, internal controls; and oversee accounting department operations, prep of financial statements, annual audit, training, compliance, reporting, processing of transactions, and budgeting and forecasting. Not-for-profit and Real Estate leasing experience required. B.A. in Accounting, three years related experience. Send resumes to: Governors Island Corporation, 10 South Street, Slip 7, New York, NY 10004.ALBION COLLEGE, Economics and Management, Albion, MI, is seeking an excellent teacher for an Assistant Professor tenure-track position starting August 2023. Teaching responsibilities include both undergraduate accounting and taxation courses: three sections per semester and on occasion summer school. Preference given to candidates who hold a CPA or other professional designations (CMA, CIA, CFA, etc.) and can teach in the areas of taxation and data analytics. The person hired will also be responsible for co-managing our Volunteer Income Tax Assistance (VITA) program offered in the Spring semester. We are especially interested in candidates who will contribute to a campus climate that supports equity, inclusion, and belonging. The person hired is expected to teach one interdisciplinary course on a schedule determined by the professor and the chair, as part of their regular teaching load, which can include a first-year seminar or an interdisciplinary honors social science course. Business/management focused courses. Interested candidates should submit an online application including a cover letter, current cv, teaching and research statements of no more than one page each, three letters of reference, copies of graduate transcripts, a DEI statement (a DEI statement should explain how you foster diversity, equity, and inclusion in your classroom and on campus through your teaching, research, and/or service), and contact information for three professional references. Application materials should be submitted through Interfolio at: https://apply.interfolio.com/97760. Applications will be accepted and reviewed on a rolling basis beginning in August 2022. Please contact John Bedient (jbedient@albion.edu), Chair, for questions about the position or search.UNIVERSITY OF SASKATCHEWAN, Edwards School of Business, Department of Accounting invites applications from qualified individuals for a tenure-track position at the rank of Assistant Professor with an anticipated start date of July 1, 2023. The successful candidate will be joining a research intensive environment and will be expected to contribute to excellence in research and scholarship through high-quality, peer-reviewed publications in their areas of expertise. Preferred candidates will have their primary research interest in the area of financial accounting and reporting, auditing, taxation, or accounting information systems/data analytics, along with a desire to teach these subjects at the undergraduate and graduate levels. Candidates must hold a Ph.D. in Accounting or equivalent. Candidates near completion of their Ph.D. are eligible to apply. Possessing a professional Canadian accounting designation is an asset. Full advertisement can be found at: UNIVERSITY, School of Business is seeking qualified candidates for two tenure-track/tenured faculty in Accounting to start July 1, 2023. These individuals will be expected to teach undergraduate and graduate courses as well as contribute to the School and within the Candidates should have a Ph.D. in Accounting or a related field and be able to provide evidence of prior teaching This is an open rank The position offers a competitive of compensation and benefits based on rank and experience. Review of applications will begin Required materials include a letter of curriculum vitae, statement of teaching statement of research, and recent course including data and will be required before a offer can be Applications that include all required information. To apply, visit: